Characterization of interleukin-4 induced gene-1 (IL-4I1) as a host immunoregulator to cutaneous leishmaniasis in cell based models - Fouad, Aya (Department of Molecular and Cell Biology, 2023)
Macrophage activation can be split into two distinct groups: Classically-Activated (M1) and Alternatively-Activated (M2) macrophages. Each are associated with a certain immune response; in the context of cutaneous leishmaniasis caused by infection with Leishmania major. Specifically, M1 macrophages allow for disease control through stimulation of cytokines such as IFN-g and release of nitric oxide for killing of intracellular parasites. Contrastingly, M2 macrophages allow for parasite survival through stimulation of cytokines such as IL-4 and IL-13 and release of urea that supports parasite growth. Candidate genes responsible for promoting M1 or M2 macrophages are being investigated as the macrophage is the sight of infection for leishmaniasis. One such candidate is IL-4i1, which has been shown to be responsible for M2 polarization. Notably, IL-4i1 catalyses phenylalanine, water, and oxygen to produce phenylpyruvate, ammonia and hydrogen peroxide. Interestingly, high levels of hydrogen peroxide create a toxic cellular environment and has been shown to lead to parasite destruction. Due to these contrasting roles of IL-4i1, IL-4i1 may be pivotal in modulating macrophage activation and host response to infection. Accordingly, we investigated IL-4i1 in a murine and human cutaneous leishmaniasis (CL) cell-based model using bone marrow-derived macrophages (BMDMs) derived from BALB/c IL-4i1+/+ and IL-4i1-/- mice and silencing of IL-4i1 in THP-1-derived macrophages. THP-1 monocytes were differentiated into macrophages via phorbol 12-myristate 13-acetate (PMA). Following macrophage verification, THP-1-derived macrophages were silenced with IL-4i1 siRNA constructs using the Silencer SelectTM siRNA Construction kit and Lipofectamine 3000 transfection agent. In IL-4 and IFN- -stimulated IL-4i1-/- BMDM infected with L. major, an increase in parasite burden was found (p< 0.05, 24 hr PI). Immunologically, nitrite was reduced, and levels of IL-12 were below detection limit whilst IL-10 was increased upon IL-4 stimulation, compared to IL-4i1+/+. Thus, the presence of IL-4i1 may play a role in controlling parasite replication and mediating M1 polarization. After 24h of infection with L. major, IL-4i1- silenced THP-1-derived macrophages showed increases in production of nitrite (p< 0.05), hence the absence of IL-4i1 induced M1 activation. Collectively, these data indicate that IL-4i may indeed favour M2 activation in the context of L. major infection as absence thereof promoted a detrimental environment for parasite burden. Altogether, this underscores IL-4i1 as a potential susceptibility factor to CL. Understanding how Leishmania parasites can modify host immune response could lead to identifying novel therapeutics such as host-directed therapies.